The co-movement between exchange rates and stock prices in an emerging market - Syajarul Imna Mohd Amin; Hawati Janor (Penerbit Universiti Kebangsaan Malaysia, 2016)
The aim of this paper is to examine the co-movement between exchange rates and stock prices of both the market and industries (industrial products and consumer products) in Malaysia from March 1994 to December 2013. Motivated by inconclusive evidences of previous studies to support the flow oriented and stock oriented hypothesis, the study applied error correction model including the Long Run Structural Model (LRSM) and variance decompositions to examine the relationship between exchange rates and stock prices. The findings suggest that the direction of causality runs from exchange rates to stock prices which are consistent with flow oriented theory. The influence of exchange rate, however, varies across industries with importing firms appearing as the most affected; indicating that Malaysian market is not homogenous. The major policy implication that can be deduced from the study is that active policy on currency management through monetary instrument (i.e. interest rates) will be helpful to stimulate the development of stock market in emerging countries like Malaysia.